Obesity and Endocrine Dysfunction Programmed by Maternal Smoking in Pregnancy and Lactation - Lisboa, Patricia C.; Oliveira, Elaine; Moura, Egberto G. (Frontiers in Physiology, 2012)
Obesity is a global epidemic, and maternal smoking has been shown to be associated with the development of childhood obesity. Overall, approximately 40% of children worldwide are exposed to tobacco smoke at home. It is well known that environmental changes within a critical window of development, such as gestation or lactation, can initiate permanent alterations in metabolism that lead to diseases in adulthood, a phenomenon called programming. It is known that programming is based on epigenetic alterations (changes in DNA methylation, histone acetylation or small interfering RNA expression) that change the expression pattern of several genes. However, little is known concerning the mechanisms by which smoke exposure in neonatal life programmes the adipose tissue and endocrine function. Here, we review several epidemiological and experimental studies that confirm the association between maternal nicotine or tobacco exposure during gestation or lactation and the development of obesity and endocrine dysfunction. For example, a positive correlation was demonstrated in rodents between increased serum leptin in the neonatal period and exposure of the mothers to nicotine during lactation, and the further development of leptin and insulin resistance, and thyroid and adrenal dysfunction, in adulthood in the same offspring. Thus, a smoke-free environment during the lactation period is essential to improving health outcomes in adulthood and reducing the risk for future diseases. An understanding of the pathophysiological mechanisms underlying the effects of smoking on programming can provide new insights into therapeutic strategies for obesity.